IMPACT OF ELECTRONIC RECORDS MANAGEMENT SYSTEM ON THE SECURITY OF RECORDS AMONG ADMINISTRATIVE STAFF - SUDETU OSENI; OLUWABUNMI D. BAKARE; AMINAT Z. ALLI (International Studies Journal)
Information and Communication Technology (ICT) has become an important tool in the day-to-day running of any office. For the past two decades, fast changes have been taking place in the office environment as a result of technological advancement. The role of the administrative staff in organizations has tremendously changed due to these changes in technology. In today’s business organizations including tertiary institutions, administrative staff are exposed to office technology and are the chief organizers of the office most especially with regard to records management – from creation, utilization, storage, safety and final disposition of such records among others.  These attributes put the administrative staff at the centre of playing a very important role in the efficient management of records as well as the office as a whole. The use of ICT has made the administrative staff to be part of today’s dynamic office. However, the efficiency and effectiveness of performing their functions as records managers depend mainly on the availability of technological gadgets in managing such records as well as strategies put in place to secure such records. It is based on this premise that this study intends to systematically investigate the impact of electronic records management system on the security of records among administrative staff of the Public Polytechnics in Edo State, Nigeria. The study will adopt a positivist research paradigm and a quantitative research approach. The study will be underpinned by the Information Security Model to ascertain the confidentiality, integrity and availability of the records.